Discours épistolaire de la guérison en Angleterre au XVIIIe siècle - Alain Kerhervé (Etudes Epistémè)
The epistolary discourse on healing has so far been overlooked by academics. However, the numerous manuscript and published sources, letters and letter-writing manuals examined in this paper testify to the central importance of healing in eighteenth-century epistolary discourse in England. Healing is considered as an epistolary issue both in the theory of the genre and in individual practices, whether abiding by the rules or not. Thus the process of healing is tackled in many letters, but the messages also suggest or transmit remedies supposed to help patients, when the letter itself does not become the main object or cure in the actual or imaginary process of recovery.